Analisis Implementasi Keselamatan dan Kesehatan Kerja di PT Empat Perdana Carton dengan Metode HIRARC - Marsudi, Hauzan Hibatullah; Kusnadi, Kusnadi (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
Work accidents are unwanted cases, often unexpected, that can cause loss of time, property, or death, and occur as part of or related to a work process in an industrial work environment. This study aims to implement the Hazard Identification and Risk Assessment Risk Control (HIRARC) process at PT Empat Perdana Carton Indonesia in Karawang to prevent and minimize work accidents due to lack of employee awareness of occupational health and safety. The method used to solve the problems that occurred at PT Empat Perdana Carton Indonesia is by using the HIRARC method. From the results of the implementation of the HIRARC method, it is known that the potential hazards that can occur in the sawing machine department are the noise produced by the sawing machine which is risky for hearing and sharp objects on the sawing machine are at risk of injuring the hands and feet. While the dangers in the production department are not using double mask which are at risk of respiratory disorders such as shortness of breath due to chemicals produced by the production process and not wearing hand PPE which is at risk of injury to the hands.